Real-world experience with long-term albumin in patients with cirrhosis and ascites - Enrico Pompili; Giacomo Zaccherini; Salvatore Piano; Pierluigi Toniutto; Antonio Lombardo; Stefania Gioia; Giulia Iannone; Clara De Venuto; Marta Tonon; Roberta Gagliardi; Maurizio Baldassarre; Greta Tedesco; et al. (JHEP Reports)
Background & Aims: Long-term albumin (LTA) is currently standard of care for patients with decompensated cirrhosis in many Italian hepatology centres. In this real-life study, we aimed to describe patient, logistical and treatment-related characteristics in daily clinical practice and to identify predictors of response. Methods: We performed a multicentre, retrospective, observational study in patients with cirrhosis and ascites receiving LTA between 01/2016 and 02/2022 and followed until death, TIPS (transjugular intrahepatic portosystemic shunt) placement, transplantation or 02/2023. Results: A total of 312 patients, the majority with alcohol-related cirrhosis, were included. At baseline, median Child-Pugh, MELD, and MELD-Na were 8, 15, and 18, respectively. Ascites was grade 2 in 55% of patients, grade 3 in 35% and refractory in 27%, while 47% had received large volume paracentesis in the previous 6 months. Median LTA was 10 months with a median dose of 40 g/week. Ascites resolved to grade 0-1 in 34% of patients within the first 3 months and 56% by the end of treatment. Predictors of ascites resolution were age (p = 0.007), baseline grade of ascites (p = 0.007), no paracentesis in the previous 6 months (p = 0.001), aetiological treatment in the past 12 months or during LTA (p = 0.005), weekly albumin dose (p = 0.014) and serum albumin concentration of 40 g/L after 1 month of treatment (p = 0.017). Of the 83 patients with refractory ascites at inclusion, 26% had grade 0/1 ascites at the last observation. No severe albumin-related side-effects were reported and only 1% discontinued for logistical reasons. Conclusions: LTA is feasible as an outpatient treatment for the management of ascites. In the current study, ascites resolved in more than half of patients receiving LTA on top of diuretics, including in some with refractory ascites. Predictors of response to LTA provide useful information for tailoring treatment. Impact and implications:: The ANSWER randomised-controlled trial has shown that long-term albumin treatment (LTA) is an effective approach for the management of patients with cirrhosis and ascites. This observational study provides novel information on target patients, modalities and length of treatment, predictors of ascites resolution, stopping criteria, and clinical trajectories of patients on treatment. LTA is a feasible option in the daily clinical practice for the management of ascites when given on top of diuretics. Rather than an alternative therapy, LTA should be integrated with the other treatment options already available for patients with difficult-to-treat ascites. The predictive factors of response identified in the present study can help physicians to individualise LTA and optimise the decision-making process.